Role of flexible cystoscopy and ultrasound in the detection of recurrent Bladder Tumour - Uddin, Md Mohsin; Islam, A K M Anwarul; Islam, Md Saiful (KYAMC Journal, 2013)
Background: Rigid cystoscopy under anaesthesia for the surveillance of recurrent bladder tumour creates a large urological workload. Recently, flexible cystoscopy became a popular alternative and an easy, safe and effective means of check cystoscopy in following-up patients of superficial transitional cell carcinoma (TCC) of the urinary bladder. Because of the frequency of tumor recurrences and the necessity of finding, whether a less invasive, easily repeatable investigation is capable of providing precise information about the bladder cavity, and, could decrease the frequency of repeated rigid cystoscopy under anaesthesia and inpatient admission; we have decided to perform this study. Methods: This is a prospective comparative study that involved 85 patients (70 male and 15 female) with a mean age of 61 years (41-80 years), who had undergone one or more transurethral resections for TCC of bladder (stage pTa and pT1; grade I and II.) in the department of Urology, BSMMU between July 2005 -Feb 2007. Ultrasonography(USG) of the bladder was performed one week before check cystoscopy. We have calculated sensitivity and accuracy of USG and flexible in comparison to rigid cystoscopy.Results: Eighty five (85) sessions of follow-up investigations- Ultrasound and flexible cystoscopy showed 31 recurrences confirmed by rigid cystoscopy and biopsy. In over 85 rigid cystoscopies, 54 were negative and 31 were positive for tumour. Sensitivity, the most important parameter, was 97% for the two examinations together. Each method separately had the following sensitivity: ultrasound 77%; flexible cystoscopy 90%.Conclusion: Considering that there was only one false-negative result of combined abdominal ultrasound and flexible cystoscopy; with this follow-up scheme we could have saved our patient from rigid cystoscopies, reducing the cost of in-patient admission and anaesthesia. DOI: http://dx.doi.org/10.3329/kyamcj.v3i1.13655 KYAMC Journal Vol. 3, No.-1, June 2012 pp.214-219